Strengthening nutrition interventions in antenatal care services affects dietary intake, micronutrient intake, gestational weight gain, and breastfeeding in Uttar Pradesh, India: Results of a cluster-randomized program evaluation - Nguyen, Phuong Hong; Kachwaha, Shivani; Tran, Lan Mai; Avula, Rasmi; Young, Melissa F.; Ghosh, Sebanti; Sharma, Praveen Kumar; Escobar-Alegria, Jessica; Forissier, Thomas; Patil, Sumeet; Frongillo, Edward A.; Menon, Purnima (Oxford University Press, 2021)
Background: Maternal nutrition interventions are inadequately integrated into antenatal care (ANC). Alive & Thrive aimed to strengthen delivery of micronutrient supplements and intensify interpersonal counseling and community mobilization through government ANC services. Objectives: We compared nutrition-intensified ANC (I-ANC) with standard ANC (S-ANC) on coverage of nutrition interventions and maternal nutrition practices. Methods: We used a cluster-randomized design with cross-sectional baseline (2017) and endline (2019) surveys (n ∼660 pregnant and 1800 recently delivered women per survey) and a repeated-measures longitudinal study in 2018–2019 (n = 400). We derived difference-in-difference effect estimates (DIDs) for diet diversity, consumption of micronutrient supplements, weight monitoring, and early breastfeeding practices. Results: Despite substantial secular improvements in service coverage from India's national nutrition program, women in the I-ANC arm received more home visits [DID: 7–14 percentage points (pp)] and counseling on core nutrition messages (DID: 10–23 pp) than in the S-ANC arm. One-third of women got ≥3 home visits and one-fourth received ≥4 ANC check-ups in the I-ANC arm. Improvements were greater in the I-ANC arm than in the S-ANC arm for any receipt and consumption of iron–folic acid (DID: 7.5 pp and 9.5 pp, respectively) and calcium supplements (DID: 14.1 pp and 11.5 pp, respectively). Exclusive breastfeeding improved (DID: 7.5 pp) but early initiation of breastfeeding did not. Maternal food group consumption (∼4 food groups) and probability of adequacy of micronutrients (∼20%) remained low in both arms. Repeated-measures longitudinal analyses showed similar results, with additional impact on consumption of vitamin A–rich foods (10 pp, 11 g/d), other vegetables and fruits (22–29 g/d), and gestational weight gain (0.4 kg). Conclusions: Intensifying nutrition in government ANC services improved maternal nutrition practices even with strong secular trends in service coverage. Dietary diversity, supplement consumption, and breastfeeding practices remained suboptimal. Achieving greater behavior changes will require strengthening the delivery and use of maternal nutrition services integrated into ANC services in the health system. This trial was registered at clinicaltrials.gov as NCT03378141.